TH CORRELATION BETWEEN HOME ENVIRONMENTAL HEALTH AND THE INCIDENCE OF ACUTE RESPIRATORY TRACT INFECTION (ARI) IN TODDLERS IN KESAMBEN VILLAGE, PLUMPANG - Miftahul Munir; Sugiyono; Adibah Enggar; Eva Silviana Rahmawati (International Nutrition and Health Administrations Journal, 2023)
Acute Respiratory Infection (ARI) is one type of environmental-based infectious disease, an acute infection that attacks one or more parts of the respiratory tract from the nose to the alveoli, including the adnexa (sinuses, middle ear cavity, pleura). This study aims to determine the relationship between the health of the home environment and the incidence of acute respiratory infections in Kesamben Village. The research design used was correlational analytic with a cross-sectional technique. The sampling technique was simple random sampling, on 38 respondents at Posyandu Cempaka, Kersamben village. Measuring tools using questionnaires, and data analysis using the chi-square statistical test. From the results of the study, it was found that most of the respondents' home environment was healthy, namely as many as 24 (68.6%) respondents, most of the 28 (36.8%) respondents at the posyandu in Kesamben village did not. suffer from ARI. Based on the chi-square test, there is a significant relationship between the independent variable and the dependent variable, namely the health of the home environment and the incidence of ARI in Kesamben Village (approx. sig = 0.013) with a significant value of = <0.05. From the description above, it can be concluded that the health of the home environment affects the health of the home environment, so it is expected to carry out ARI in toddlers. Therefore, every community needs to maintain and maintain physical sanitation of the house and apply a clean and healthy lifestyle in daily life to reduce the risk of getting infected. diseases related to the environment, especially in toddlers.